Il fondo Adelaide Ristori al Museo Biblioteca dell’Attore di Genova - Donatella Mezzani (Drammaturgia)
The Adelaide Ristori Archive has been kept at the Museo Biblioteca dell’Attore in Genoa since 1967, after the donation of Irma Castren Capranica del Grillo. In the same year this archival collection was officially acknowledged as cultural heritage for its great historical interest and therefore subjected to a bond of protection. This essay begins with a brief history of the previous archival organization attempts, none of which was completed nor conducted following scientific and consistent basis. Donatella Mezzani, who supervised the archival interventions (including its reorganization and filing, currently available online), supported by the Archival and Bibliographic Superintendence of Liguria, goes on to describe the methodology and criteria adopted. The archival series in which the documentary heritage is currently structured are then briefly outlined, indicating the consistency, dating and state of conservation of the material supports. Some particularly interesting papers are also mentioned and related to the biography and professional path of the great Italian actress. The Adelaide Ristori Archive is extremely rich in terms of volume and completeness of information: Besides, it is a valuable source for different research perspectives and has both some of the specific characteristics of business records and the hybrid and individual ones of family and personal archives. It is undoubtedly a privileged ‘witness’ of Adelaide Ristori’s life, of her family and her entourage: a unique parable, always divided between life and art.